2014
DOI: 10.1016/j.clim.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 7A is expressed on airway eosinophils and upregulated by IL-5 family cytokines

Abstract: Semaphorin 7A (Sema7A) plays a major role in TGF-β1-induced lung fibrosis. Based on the accumulating evidence that eosinophils contribute to fibrosis/remodeling in the airway, we hypothesized that airway eosinophils may be a significant source of sema7A. In vivo, sema7A was expressed on the surface of circulating eosinophils and upregulated on bronchoalveolar lavage eosinophils obtained after segmental bronchoprovocation with allergen. Based on mRNA levels in unfractionated and isolated bronchoalveolar cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 38 publications
6
72
0
Order By: Relevance
“…The expression of SEMA7A in the lungs of IgE-sensitized mice was increased compared with that in nonsensitized mice; consistent with previous data (Holmes et al, 2002;Sato and Takahashi, 1998;Mine et al, 2000;Esnault et al, 2014), the epithelial cells, blood vessels, and inflammatory cells in the lungs of IgEsensitized mice showed this expression. Furthermore, it has been reported that SEMA7A facilitates increased transendothelial migration of neutrophils depending on the PLXNC1 for the receptor (Morote-Garcia et al, 2012); PLXNC1 is expressed in neutrophils in peripheral blood of normal mice , and is associated with adhesion in the inflammatory cell transmigration process (Holmes et al, 2002;Lazova et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The expression of SEMA7A in the lungs of IgE-sensitized mice was increased compared with that in nonsensitized mice; consistent with previous data (Holmes et al, 2002;Sato and Takahashi, 1998;Mine et al, 2000;Esnault et al, 2014), the epithelial cells, blood vessels, and inflammatory cells in the lungs of IgEsensitized mice showed this expression. Furthermore, it has been reported that SEMA7A facilitates increased transendothelial migration of neutrophils depending on the PLXNC1 for the receptor (Morote-Garcia et al, 2012); PLXNC1 is expressed in neutrophils in peripheral blood of normal mice , and is associated with adhesion in the inflammatory cell transmigration process (Holmes et al, 2002;Lazova et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Among them, semaphorin 7A (SEMA7A) was originally shown to promote axon outgrowth and contribute to the formation of lateral olfactory tracts (Pasterkamp et al, 2003). However, SEMA7A is expressed broadly by lymphoid cells, eosinophils, myeloid cells, bone cells, the nervous system, epidermal keratinocytes, fibroblasts, and endothelial blood vessels (Holmes et al, 2002;Sato and Takahashi, 1998;Mine et al, 2000;Esnault et al, 2014). Additionally, it is a potent stimulator of monocytes and neutrophils and induces cytokine production (Holmes et al, 2002); T-cell responses are negatively regulated by it (Czopik et al, 2006), suggesting the possibility that SEMA7A contributes to the development of allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In uterine smooth muscle cells myocyte enhancer factor 2 is also bound in this complex (57). Previous studies have also reported the upregulation of several transcription factors associated with the transition from pregnant not-in-labor to laboring myometrium in rat, mouse and human (8,16,25,28,32,53,62,69).…”
Section: Discussionmentioning
confidence: 98%
“…We used the several cytokines (IL-3, IL-5, GM-CSF, TNF-a, b-NGF, and VEGF) which were reported the activated effect for eosinophils or the enhanced expression for semaphorin receptors for priming. 10,11 There is a possibility that up-regulation of semaphorin receptors and direct effect of semaphorin are led in eosinophils by other priming methods. Previous study reported that sema7A expressed on eosinophils and sema7A protein on the surface of blood eosinophils was increased more by IL-3 than by GM-CSF or IL-5.…”
Section: Dear Editormentioning
confidence: 98%
“…Previous study reported that sema7A expressed on eosinophils and sema7A protein on the surface of blood eosinophils was increased more by IL-3 than by GM-CSF or IL-5. 10 Peer review under responsibility of Japanese Society of Allergology.…”
Section: Dear Editormentioning
confidence: 99%